Diversidade genética e efeitos da fragmentação de Matas Secas em Enterolobium contortisiliquum ( Farbaceae): implicações para conservação - Patricia de Abreu Moreira (2012)
The increasing process of natural areas fragmentation is the major responsible of biodiversity losses. In addition to its rapid destruction, the habitats that previously have occupied large areas are fragmented due to human activities. The results of these factors are vegetation mosaic ecosystems immersed in an altered matrix, Due to environmental changes the populations are reduced and subdivided, which may result in changes of ecological and genetic processes. Thus, ecological and genetic diversity studies of species are fundamental to conservation strategies development. In this context, the seasonally dry tropical forests (SDTF) are in threat because of its disjunct distribution in the environment and anthropic actions that replace natural areas for the human settlements and agricultural activities. Entemlobium contortisiliquum species is typical of SDTF and is increasingly threatened in their natural habitat due to fragmentation and indiscriminate removal of individuals. The fmits of this species are resources for cattle feeding during dry season, but its poisonous pods cause abortions and photosensitizers injuries. Thus many farmers choose to remove these trees from the pastures. So, the present study aimed to evaluate the genetic diversity of the E. cantartisiliquum species and verify the effects of habitat fragmentation on its reproductive success and phenological pattems. High genetic diversity was found using ISSR molecular markers in E. contartisiliquum populations in SDTF remnants. Most of this variation was found within populations and differentiation between them was detected. Emerolabium cantortisiliquum populations formed four distinct groups and Sao Francisco River may be a barrier responsible for the observed structure. The effect of fragmentation on the reproductive success of E. cantartisiliquum was not observed on the following parameters: fruit and seed size, undamaged seed production, seed abortion, seed predation, total seed production and number of seed germinated of trees located in a conserved matrix compared to trees located in a degraded matrix. However, seeds of trees located in a conserved matrix germinated faster than seeds of trees located in a degraded matrix. Furthermore, the effect of forest fragmentation was observed on phenological patterns. Trees of conserved matrix exhibited a distinct phenological pattem of trees of fragmented matrix and trees of urban area. Changes in reproductive phenology may cause a temporal isolation between individuals of different populations inhibiting the gene flow among them. The microsatellite markers developed for E. cyclocurpum were successfully transferred to E. contortisiliquum and may be used to investigate genetic diversity, the mating system, gene flow and spatial genetic structure of trees in areas with different degrees of disturbance, in order to verify the effects of fragmentation on these parameters and generate support for its conservation. The results of this study are important for adoption of conservation strategies and management of the species E. cantortisiliquum and to understand the effects of fragmentation in ecological patterns and genetic diversity of tree species present in tropical dry forests.